An evaluation study of the Becton-Dickinson ProbeTec Qx (BDQx) Trichomonas vaginalis trichomoniasis molecular diagnostic test in two large, urban STD services. (20th January 2017) - Tipple, Craig; Rayment, Michael; Mandalia, Sundhiya; Walton, Lisa; O'Neill, Sinead; Murray, John; O'Riordan, Alan; Rebec, Monica; Harrington, Laura; Jones, Rachael; Wilkinson, Dawn
Abstract : Objectives: The BASHH guidelines recommend molecular tests to aid diagnosis of Trichomonas vaginalis (TV) infection; however many clinics continue to use relatively insensitive techniques (pH, wet-prep microscopy (WPM) and culture). Our objectives were to establish a laboratory pathway for TV testing with the Becton-Dickinson Qx (BDQx) molecular assay, to determine TV prevalence and to identify variables associated with TV detection. Methods: A prospective study of 901 women attending two urban sexual health services for STI testing was conducted. Women were offered TV BDQx testing in addition to standard of care. Data collected were demographics, symptoms, results of near-patient tests and BDQx results for TV, Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (GC) . Women with any positive TV result were treated and followed up for test of cure (TOC). Results: 901 women had a TV BDQx test. 472 (53%) were white, 143 (16%) black and 499 (55%) were symptomatic. Infections detected by BDQx were: 11 TV (1.2%), three GC (0.3%) and 44 CT (4.9%). Of the 11 BDQx-detected TV infections, 8 (73%) were in patients of black ethnicity. Of these, four of seven cases (57%) were WPM-positive. All patients received treatment and nine of nine (100%) were BDQx-negative at TOC. In univariate analysis, only black ethnicity was associated with likelihood of a positive TV BDQx result (relative risk (RR) 10.2 (95% CI 2.15 to 48.4)). Conclusions: The use of the BDQ enhanced detection of TV in asymptomatic and symptomatic populations. Cost-effective implementation of the test will rely on further work to reliably detect demographic and clinical variables that predict positivity.